2014
DOI: 10.1515/jbcpp-2013-0164
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, anti-inflammatory, and anti-oxidant activities of Phlogacanthus thyrsiflorus leaves

Abstract: Based on the findings, we can conclude that PT leaf possesses analgesic, anti-inflammatory, and antioxidant activities. Preliminary phytochemical study of PT leaves revealed the presence of flavonoids, tannins and triterpens in methanol extract which could be correlated with its observed biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Data mining or literature review on all 61 species of medicinal plants for their reported pharmacological activities revealed that 52 of them have been already subjected to scientific studies and only eight species remained unstudied ( Table 1 ). 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 Most of the LAMP grow in the temperate, subtropical and tropical agroclimatic regions and are distributed worldwide. Consequently, same or similar medicinal plants are found common in traditional medicines practiced in the Asia–Pacific and African countries, although they may be used for treating different ailments in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Data mining or literature review on all 61 species of medicinal plants for their reported pharmacological activities revealed that 52 of them have been already subjected to scientific studies and only eight species remained unstudied ( Table 1 ). 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 Most of the LAMP grow in the temperate, subtropical and tropical agroclimatic regions and are distributed worldwide. Consequently, same or similar medicinal plants are found common in traditional medicines practiced in the Asia–Pacific and African countries, although they may be used for treating different ailments in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION: Root extracts of Phlogacanthus thyrsiflorus Nees., showed important phytoconstituents such as Phenolics, flavonoids, and tannins which are a major group of compounds that act as natural antioxidants or free radical scavengers which possess antimicrobial, antiallergic, anti-mutagenic, anti-inflammatory and anti-carcinogenic properties 22,23 . In another study, the presence of tannins, flavonoids, saponins, carbohydrates, steroids, alkaloids, reducing sugar, and terpenoids were reported in the leave extracts of Phlogacanthus thyrsiflorus 24 . The higher amount of phenolic and flavonoid contents are detected in the present study which corresponds to stronger antioxidant capacity.…”
Section: Ferric Reducing Antioxidant Propertymentioning
confidence: 93%
“…Presence of total avonoid is found to be higher in methanol leaf extract of Justicia adhatoda Linn. In a study conducted by (Das et al 2015) to investigate the potential role of a methanol extract from Phlogacanthus thyrsiformis Nees. leaves, avonoid were discovered in trace concentrations.…”
Section: Total Avonoid Contentmentioning
confidence: 99%